2015
DOI: 10.1681/asn.2014050489
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Gene Cause in 29.5% of Cases of Steroid-Resistant Nephrotic Syndrome

Abstract: Steroid-resistant nephrotic syndrome (SRNS) is the second most frequent cause of ESRD in the first two decades of life. Effective treatment is lacking. First insights into disease mechanisms came from identification of single-gene causes of SRNS. However, the frequency of single-gene causation and its age distribution in large cohorts are unknown. We performed exon sequencing of NPHS2 and WT1 for 1783 unrelated, international families with SRNS. We then examined all patients by microfluidic multiplex PCR and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
642
10
17

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 545 publications
(719 citation statements)
references
References 40 publications
30
642
10
17
Order By: Relevance
“…The answer to this question remains unclear. With regard to pediatric patients, Hildebrandt and coworkers (75) have suggested that every family with a child who has FSGS deserves to be offered an opportunity to have a genetic diagnosis (RE). Benefits of this approach may include a guide to appropriate therapy (e.g., avoidance of glucocorticoids except for in genetic forms that may be responsive and coenzyme Q10 therapy for particular mitochondrial mutations), prognosis (typical native kidney outcomes and likelihood of transplant recurrence), and family issues (identification of disease in other family members and prenatal testing).…”
Section: Genetic Fsgsmentioning
confidence: 99%
“…The answer to this question remains unclear. With regard to pediatric patients, Hildebrandt and coworkers (75) have suggested that every family with a child who has FSGS deserves to be offered an opportunity to have a genetic diagnosis (RE). Benefits of this approach may include a guide to appropriate therapy (e.g., avoidance of glucocorticoids except for in genetic forms that may be responsive and coenzyme Q10 therapy for particular mitochondrial mutations), prognosis (typical native kidney outcomes and likelihood of transplant recurrence), and family issues (identification of disease in other family members and prenatal testing).…”
Section: Genetic Fsgsmentioning
confidence: 99%
“…PLCe1 was also shown to modulate adrenergic receptor-dependent cardiac contraction and to inhibit cardiac hypertrophy (22,23). Patients with focal segmental glomerulosclerosis have been found to have loss-of-function mutations in PLCe1, and PLCe1 itself interacts with transient receptor potential channel 6 (24)(25)(26)(27). Even more intriguing is the fact that a genome-wide association study identified the susceptibility loci for dengue shock syndrome at PLCe1 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the apolipoprotein L1 gene (APOL1)-associated spectrum of nondiabetic nephropathy in patients with recent African ancestry supports the need to remove "hypertension" as the cause of ESRD in those with mild to moderately elevated BPs. Detection of genes underlying steroid-resistant nephrotic syndrome and autosomal dominant tubulointerstitial forms of nephropathy further supports the need to update the nomenclature, particularly after genetic testing becomes widely available (8,9).…”
Section: Limitations Of Esrd Classification On the Current Cms 2728 Formmentioning
confidence: 99%